Pengaruh Konsentrasi Dan Frekuensi Penyiraman Limbah Cair Tahu Terhadap Pertumbuhan Vegetatif Rosella (Hibiscus sabdariffa) - Fadilah, Nurul, Dra. Suparti, M. Si (2015)
Tofu is a food processed soybean, in the process of tofu making out, liquid waste that contains organic matter, so that the waste water is expected to be beneficial to the soil to meet the nutrient in plants roselle. The purpose of this study to determine the effect of concentration and frequency of watering liquid waste out of the tofu for growth of roselle (Hibiscus sabdariffa). This research was arranged in a completely randomized design (CRD) with 2 factors and 3 replications. The first factor is the concentration of the liquid waste out of tofu consists of 3 levels: 1,5%, 2%, 2,5%. The second factor is the frequency of watering consists of 3 levels: 2 days, 5 days, 7 days. Data were analyzed by 2-way analysis of variance test (ANOVA), to see the effect of treatments then continued by Least Significant Difference test (LSD). Analysis of variance (ANOVA) showed that the concentration and frequency of watering liquid waste out of the tofu effluent know an impact on growth plant height, number of leaves, and leaf width roselle plant. The best treatment for stem height is K1F1 (concentration of wastewater know 1,5% with the frequency of watering 2 days) is 42.2 cm. The best treatment for a number of leaves is K3F3 (concentration of wastewater know 2,5% with the frequency of watering 7 days) of 10 leaves. The best treatment for leaf width is K3F2 (concentration of wastewater know 2,5% with the frequency of watering 5 days) which is 5 cm.